Synaptogyrin-3 plays a critical role in addiction-related dopamine dysfunction and behavioral maladaptations - Emily G. Peck; Soren D. Emerson; Alyson M. Curry; Kimberly M. Holter; Paige M. Estave; Jonathon P. Sens; Olivia A. Colarusso; Sean P. Farris; Drew D. Kiraly; Robert W. Gould; Brian A. McCool; Erin S. Calipari; et al. (Proceedings of the National Academy of Sciences, 2026)
Cocaine use disorder is marked by deficits in dopamine signaling; however, the molecular mechanisms driving these deficits remain unclear. The synaptic vesicle protein Synaptogyrin-3 (Syngr3) has recently garnered attention for its association with disorders involving dopamine dysfunction and impaired cognition. Here, we found low Syngr3 expression in the ventral tegmental area (VTA) of men who died of cocaine overdose and in male rats that had chronically self-administered cocaine. Syngr3 was confirmed to be in dopamine neurons, and its expression was correlated with dopamine markers in both humans and rats. Syngr3 levels showed a robust inverse correlation with motivation to self-administer cocaine in the rat model. Moreover, viral overexpression of Syngr3 in VTA dopamine neurons improved cognitive flexibility and substantially reduced cocaine reinforcement and drug-taking behavior. Finally, Syngr3 overexpression prevented cocaine-induced dopamine deficits. These findings establish Syngr3 as a key dopamine regulator and potential therapeutic target for cocaine use disorder.